Optimal power flow using the gradient method to reduce electrical losses in power systems (2008)
This article presents an optimal power flow model by the gradient method for reducing losses in power systems. The algorithm allows a set of control variables to be adjusted in order to obtain an operating point that minimizes power losses. The method is based on the solution of the power flow by the Newton method. The limits of the independent variables are managed through penalty functions. The performance of the algorithm is evaluated using two different methods to calculate the size of the step along the feasible direction: a constant step and a variable step using the debolabola adjustment method.